Use of clomipramine as chemotherapy of the chronic phase of Chagas disease - Fauro, Romina (2013)
Chagas infection is a major endemic disease affecting Latin American countries. The persistence of Trypanosoma cruzi generates a chronic inflammatory reactivity that induces an immune response directed to the host’s tissues. The effectiveness of the treatment in the chronic phase is still unsatisfactory due, amongst other reasons, to the collateral effects of the drugs used. We investigated the effect of clomipramine, a tricyclic antidepressant that, when used as a treatment of T. cruzichronically infected mice, inhibits trypanothione reductase, an exclusive and vital enzyme of T. cruzi. Clomipramine improved survival (P< 0·05) by diminishing the parasite intensity as demonstrated by PCR studies in the heart and skeletal muscle, and significantly prevented the evolution to fibrosis of the inflammatory infiltrates. Clomipramine could be a good candidate for the treatment of chronic Chagas disease.